Antibiotic Drug Resistance Pattern of Uropathogens in Pediatric Patients in Pakistani Population - Zakia Iqbal; Ahsan Sattar Sheikh; Anwaar Basheer; Hadiqa tul Hafsa; Mehboob Ahmed; Anjum Nasim Sabri; Samiah Shahid (MDPI AG, 2023)
The common prevalent diseases in the age of 0 to 6 are related to urinary tract infections. If not properly diagnosed, they will lead to urological and nephrological complications. Uropathogens are developing resistance against most drugs and are harder to treat. A study was done on the inpatients and outpatients of the two hospitals located in Lahore. A total of 39,750 samples that were both male and female were collected. Escherichia and Klebsiella were found in 234 samples based on biochemical characterization, growth on CLED agar, and white blood cell/pus cell (WBC) microscopy. In comparison to males, female samples had a higher number of uropathogens (1:1.29). From the samples of Shaikh Zayed Hospital (SZH), the ratio of Klebsiella to Escherichia (1:1.93) was reported, while this ratio was 1.84:1 from the Children Hospital (CH). The incidence of UTI was higher in the month of September. Randomly selected Escherichia and Klebsiella were verified via a 16S rRNA sequence. Antibiotic resistance profiling of isolated bacterial strains was done against 23 antibiotics. The most efficient antibiotics against Klebsiella and Escherichia were colistin sulphate (100% sensitivity against bacteria from CH; 99.3% against strains from SZH) and polymyxin B (100% sensitivity against strains from SZH; 98.8% against strains from CH). Sensitivity of the total tested strains against meropenem (74%, SZH; 70% CH), Fosfomycin (68%, SZH; 73% CH strains), amikacin (74% SZH; 55% CH), and nitrofurantoin (71% SZH;67% CH) was found, Amoxicillin, ampicillin, and cefuroxime showed 100 to ≥90% resistance and are the least effective.